2023
DOI: 10.1002/eat.23891
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled trial of a cognitive‐behavioral therapy guided self‐help mobile app for the post‐acute treatment of anorexia nervosa: A registered report

Abstract: Introduction: Relapse following acute treatment for anorexia nervosa (AN) is common. Evidence suggests cognitive-behavioral therapy (CBT) may be useful in the post-acute period, but few patients have access to trained providers. mHealth technologies have potential to increase access to high-quality care for AN, including in the post-acute period. The aim of this study is to estimate the preliminary feasibility and effectiveness of a CBT-based mobile intervention plus treatment as usual (TAU), offered with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…The study employs two psychotherapeutic interventions, Cognitive Behavioral Therapy (CBT) (Ahmadi & Valizadeh, 2021;Asghari N et al, 2020;Fitzsimmons-Craft et al, 2023) and Acceptance and Commitment Therapy (ACT) (Ahmadi & Valizadeh, 2021;Far et al, 2016), each structured into eight sessions lasting 60-75 minutes. These sessions are designed to address interpersonal sensitivity and loneliness in adult women with depression.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study employs two psychotherapeutic interventions, Cognitive Behavioral Therapy (CBT) (Ahmadi & Valizadeh, 2021;Asghari N et al, 2020;Fitzsimmons-Craft et al, 2023) and Acceptance and Commitment Therapy (ACT) (Ahmadi & Valizadeh, 2021;Far et al, 2016), each structured into eight sessions lasting 60-75 minutes. These sessions are designed to address interpersonal sensitivity and loneliness in adult women with depression.…”
Section: Interventionsmentioning
confidence: 99%
“…1 Introduction epression remains one of the most pervasive mental health challenges globally, affecting millions of individuals and imposing significant psychological and socio-economic burdens (Fitzsimmons-Craft et al, 2023;Scheer et al, 2023;Taheri et al, 2023;Xie et al, 2023;Ziapour et al, 2023). The World Health Organization identifies depression as a leading cause of disability worldwide, necessitating effective therapeutic interventions (Benjet et al, 2023;Ebrahimi et al, 2023;Ertezaee et al, 2023).…”
mentioning
confidence: 99%
“…Experimental techniques, by changing painful memories of childhood, focus on altering mental images, physical sensations, and emotional feelings, and help ensure that recalling past bitter memories does not have a destructive effect on the individual. Since the emphasis of experimental techniques in improving communication skills in women affected by infidelity is on emotions, it seems that these techniques have not been able to help the individual become aware of their emotions and accept them, and with emotional reorganization, self-examination, and new learning, emotional regulation in interpersonal relationships, as well as self-soothing, create the conditions for improving schemas (Fitzsimmons-Craft et al, 2023;Lundström et al, 2022). In fact, experimental techniques such as the use of mental imagery have not been able to make the individual recognize the primary schemas and understand their developmental roots, relate them to their current life, improve patient understanding, move from rational cognition to emotional experience, and from cold cognition to hot cognition.…”
Section: Tablementioning
confidence: 99%
“…CBT is also appropriate for those seeking short-term therapeutic options that do not necessarily require medication. One of the greatest advantages of CBT is helping patients develop adaptive skills useful both presently and in the future (Entezari et al, 2021;Fitzsimmons-Craft et al, 2023). Based on previous studies (Ahmadi & Valizadeh, 2021;As'hab et al, 2022;Babaee et al, 2022;Barnes et al, 2023;Entezari et al, 2021;Fitzsimmons-Craft et al, 2023;Hamidi et al, 2022;Hu et al, 2021;Jabraeili et al, 2014;Khandaghi Khameneh et al, 2023;Linehan, 1993;McEvoy et al, 2022;Nateghi & Sohrabi, 2017;Ofem, 2023;Rahimi et al, 2022;Roman et al, 2021;Rowland, 2010;Scheer et al, 2023;Spirito et al, 2011;Walser et al, 2015), it can be concluded that CBT and especially ACT, as new generations of psychological treatments, enhance psychological flexibility.…”
Section: Introductionmentioning
confidence: 99%